Rancang Bangun Digital Signage Sebagai Papan Informasi Digital Masjid Di Kota Palangka Raya Berbasis Web Responsive - Mochammad Ichsan; Sam'ani Sam'ani; Ferdiyani Haris; M. Haris Qamaruzzaman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Until now, mosques are still often found in providing information such as prayer schedules, study schedules, financial reports, appeals still use wooden boards or triplex so that it can only be known by people who enter or worship at the mosque and the information is still very monotonous. There are still a few mosques that already have information screens in the form of television screens that present prayer times, running texts about study info, but they are still limited and have not been equipped with study pamphlets and mosque cash reports. Most mosques in the city of Palangka Raya and its surroundings still do not have information screens because the cost of the equipment is relatively too expensive, so they only use bulletin boards and paper pasted on the mosque walls to display or inform prayer schedules, routine studies and Friday sermons and other important information. So it is necessary to have a tool application in the form of information screens throughout the mosques in Palangka Raya and its surroundings that can display prayer schedules, regular studies and Friday sermons and other important information in an integrated manner so that people can see the desired mosque information through smartphone media, Besides that, mosque administrators or ta'mir can manage their own content or information media content according to the needs of the mosque by utilizing digital signage so that the form of delivering information through electronic display media is carried out dynamically and attractively. The method used in this research is to use the System Development Life Cycle (SDLC). Software development uses the Waterfall software development model.